172k views
0 votes
3x - y = 2

y = x - 1
When the expression x - 1 is substituted into the first equation for y, the resulting equation is

User Jondow
by
5.1k points

2 Answers

3 votes

Given.

3x - y = 2

Substitute x - 1 for variable y.

3x - x - 1 = 2 ← Resulting equation

User Oowowaee
by
5.6k points
6 votes

Answer:

see explanation

Explanation:

Given

3x - y = 2

Substitute y = x - 1 into the equation

3x - (x - 1) = 2

3x - x + 1 = 2 ← simplify left side

2x + 1 = 2 ← required equation after substitution

User Abhriya Roy
by
5.4k points